2016
DOI: 10.1039/c6nr04017a
|View full text |Cite
|
Sign up to set email alerts
|

A dual-readout chemiluminescent-gold lateral flow test for multiplex and ultrasensitive detection of disease biomarkers in real samples

Abstract: Even though the gold lateral flow test (GLFT) is low-cost and allows for point-of-care testing (POCT), its intrinsic limitations including low sensitivity and incapability of quantification significantly hinder the clinical application of GLFT for assaying disease biomarkers. To improve the performance of the GLFT without sacrificing its simplicity, we develop a chemiluminescent-gold lateral flow test (C-mode GLFT) for quantitative and multiplex detection of disease biomarkers with an ultrahigh sensitivity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 30 publications
(61 reference statements)
0
54
0
Order By: Relevance
“…Furthermore, the RSD at the different spiked concentrations of CC was below 10%, which showed that this strip has good repeatability. For comParison, GLFS was also applied for CC detection with 30 nm of gold nanoprticle (The preparation for gold nanoparticle-Ab was based on previous report of our group [25]). The visual and quantitative LOD of GLFS were 20 ng/mL and 3.75 ng/mL (S = 0.02, M = 0.016), respectively, which were higher than those of MLFS (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the RSD at the different spiked concentrations of CC was below 10%, which showed that this strip has good repeatability. For comParison, GLFS was also applied for CC detection with 30 nm of gold nanoprticle (The preparation for gold nanoparticle-Ab was based on previous report of our group [25]). The visual and quantitative LOD of GLFS were 20 ng/mL and 3.75 ng/mL (S = 0.02, M = 0.016), respectively, which were higher than those of MLFS (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al proposed a chemiluminescent-gold lateral flow sensor for AFP and CEA detection with a novel signal amplification strategy. In their work, GNP was used and decorated with HRP and Ab1 to improve the traditional lateral flow based sensor with the increase of sensitivity by three orders of magnitude [ 192 ]. Yang and coworkers fabricated a paper-based barcode assay for detection of multiplex target biomarker combing with GNP, and this sensor also showed its potential in the point-of-care field with the low-cost, rapid detection, and good stability [ 193 ].…”
Section: Other Biomarker Sensorsmentioning
confidence: 99%
“…Among other reported methods for β-adrenergic agonists detection [11][12][13][14][15][16][17] , the immunoassay has been paid great attention due to its easy-operation protocols, comparable simple pretreat of the samples and high specificity. Therefore, the enzyme-linked immunosorbent assay (ELISA) and the immunochromatographic lateral flow strip (LFS) have been well commercialized as the kit for rapid and sensitive detection of β-adrenergic agonists [18][19][20][21][22] . However, these two-mentioned commercial immune kits can only realize the detection of one analyte at each assay.…”
Section: Introductionmentioning
confidence: 99%